Patient satisfaction and total hip arthroplasty: a review - Lauren Okafor; Antonia F. Chen (Arthroplasty, 2019)
Abstract Primary total hip arthroplasty (THA) has been recognized as a reliable intervention for patients with end-stage osteoarthritis. Despite several notable advances in this procedure, studies have identified at least 7% of patients who remain dissatisfied. There is no general consensus on how to measure patient satisfaction in orthopedic surgery. However, validated tools have been used in multiple studies to further investigate this problem. A comprehensive review was conducted to examine the factors associated with patient satisfaction following THA. Associations in literature included patient expectation, age, sex, pain management, patient comorbidities (medical or psychiatric that existed prior to surgery), and length of stay. The continuous collection of patient satisfaction data using validated and reliable measurement tools is necessary to improve this important patient-reported outcome after THA.